Given:
[tex]8\frac{9}{12}-3\frac{1}{6}[/tex]We will be subtracting mixed numbers as follows:
First) convert the mixed numbers to fractions as follows:
[tex]\begin{gathered} 8\frac{9}{12}=\frac{12\cdot8+9}{12}=\frac{105}{12} \\ \\ 3\frac{1}{6}=\frac{6\cdot3+1}{6}=\frac{19}{6} \end{gathered}[/tex]Second) make the denominators the same number by finding the lowest common denominator
The least common denominator of 6 and 12 = 12
So, the first fraction will not change
the second fraction will be as follows:
[tex]\frac{19}{6}=\frac{19\cdot2}{6\cdot2}=\frac{38}{12}[/tex]Finally, the subtraction process will be as follows:
[tex]8\frac{9}{12}-3\frac{1}{6}=\frac{105}{12}-\frac{38}{12}=\frac{105-38}{12}=\frac{67}{12}[/tex]Convert the fraction to a mixed number
[tex]\frac{67}{12}=5\frac{7}{12}[/tex]So, the answer will be:
[tex]5\frac{7}{12}[/tex]